Use of medical care for chest pain: differences between blacks and whites. - Strogatz, D S (1990)
Data from a 1980, community-based survey of adult residents of Edgecombe County, North Carolina were analyzed to examine differences between Blacks and Whites in the reported use of medical care after experiencing chest pain. Of all adults (N = 302) with chest pain in the year prior to interview, 49 percent of Blacks and 27 percent of Whites did not see a physician following the chest pain (difference = 22%, 95% CI = 12, 33). A multivariable analysis found that although the association between race and utilization was reduced at poverty levels of income, it was not explained by differences in demographic characteristics, health status or other dimensions of access to care.